2021
DOI: 10.3390/jof7100877
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Etiology COVID-19 Associated Pulmonary Aspergillosis (CAPA)—A Case Report and Brief Review of the Literature

Abstract: The SARS-CoV-2 pandemic has proved to be a significant risk addition for invasive infections with Aspergillus. Even though there are plenty of data about the COVID-19-associated pulmonary aspergillosis (CAPA), especially involving Aspergillus fumigatus, recent studies are presenting cases of CAPA involving more than one species of Aspergillus. We report the first case of a SARS-CoV-2 patient associating co-infection with, most likely, Aspergillus section Fumigati and Aspergillus section Flavi from Romania, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Multiple articles regarding the association between invasive mold infections (especially aspergillosis) and severe or critical forms of COVID-19 were published [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Similarly to our cases, when COVID-19 was associated with aspergillosis, the mortality rate was very high [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple articles regarding the association between invasive mold infections (especially aspergillosis) and severe or critical forms of COVID-19 were published [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Similarly to our cases, when COVID-19 was associated with aspergillosis, the mortality rate was very high [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few recent research have shown instances of COVID‐19 infection involving more than one aspergillus species or two separate fungal infections at the same time. Toc et al reported a case of COVID‐19‐associated pulmonary aspergillosis with Aspergillus fumigatus and Aspergillus flavus with favorable outcome 2 . Johnson et al 3 reported a case of combined probable pulmonary aspergillosis and possible mucormycosis in a diabetic male with COVID‐19 in the ICU who was treated with liposomal amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary infections or co‐infections are commonly identified in the severe influenza and other severe respiratory viral infections with high mortality and morbidity rates 1 . Co‐infection between severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and other pathogens has become another serious threat to treat the patients, which should not be neglected 2 . These co‐pathogens include bacteria such as Streptococcus pneumoniae and Staphylococcus aureus, fungal pathogens including Aspergillus or Mucorales species, and the viruses such as influenza, and rhinovirus/enterovirus 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From highly resistant strains of Candida auris to COVID-19-associated pulmonary aspergillosis (CAPA) or mixed etiology CAPA, there is little doubt that we are facing an overwhelming pressure on many clinical settings caused by various fungal infections. Mycoses gradually become more difficult to treat and, similar to bacteria, some of the circulating fungal strains are on the verge of panresistance [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%